2014
DOI: 10.1021/es403877s
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic Uptake by Rice Is Influenced by Microbe-Mediated Arsenic Redox Changes in the Rhizosphere

Abstract: Arsenic (As) uptake by rice is largely determined by As speciation, which is strongly influenced by microbial activities. However, little is known about interactions between root and rhizosphere microbes, particularly on arsenic oxidation and reduction. In this study, two rice cultivars with different radial oxygen loss (ROL) ability were used to investigate the impact of microbially mediated As redox changes in the rhizosphere on As uptake. Results showed that the cultivar with higher ROL (Yangdao) had lower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
119
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 188 publications
(137 citation statements)
references
References 47 publications
9
119
0
3
Order By: Relevance
“…Elevated As concentrations in paddy soils has originated from both geological and anthropogenic activities, the latter being the major contributor due to smelting, mining and irrigation using As-contaminated groundwater (Liao et al, 2005;Jia et al, 2014). Due to its inherent physiological characteristics and preference to anaerobic conditions rice is particularly efficient at As uptake and accumulation compared to other crops (Su et al, 2010;.…”
Section: Whilst Widespreadmentioning
confidence: 99%
“…Elevated As concentrations in paddy soils has originated from both geological and anthropogenic activities, the latter being the major contributor due to smelting, mining and irrigation using As-contaminated groundwater (Liao et al, 2005;Jia et al, 2014). Due to its inherent physiological characteristics and preference to anaerobic conditions rice is particularly efficient at As uptake and accumulation compared to other crops (Su et al, 2010;.…”
Section: Whilst Widespreadmentioning
confidence: 99%
“…strain PHS-1 (Kulp et al, 2008;Zargar et al, 2010), which was suggested to be conducted by a new arsenite oxidase clade, ArxA (Zargar et al, 2012), though no information is presently known on the this enzyme's functioning (van Lis et al, 2013). Through these processes, As speciation and bioavailability are altered, affecting its toxicity, environmental behavior and fate in the environment, and also its accumulation into food crops (such as rice) (Jia et al, 2014(Jia et al, , 2013Stolz and Oremland, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…In paddy soils, As is released into soil solution mainly in the form of arsenite (As(III)), by As-reducing bacteria and by the reductive dissolution of iron oxyhydroxides which reduces the binding sites of As on minerals (Stroud et al 2011;Xu et al 2008). Elevated concentration of As(III) in the soil solution under anaerobic condition provides As sources to rice plants (Roberts et al 2010;Jia et al 2014). Also, rice absorbs As(III) more efficiently than other cereal crops because of its strong silicon uptake pathway which also allows the quick uptake of As(III) (Ma et al 2008;Su et al 2010).…”
Section: Introductionmentioning
confidence: 99%